2013
DOI: 10.1164/rccm.201304-0650oc
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of Tuberculosis Treatment by Adjunctive Therapy with Verapamil as an Efflux Inhibitor

Abstract: Rationale: A major priority in tuberculosis (TB) is to reduce effective treatment times and emergence of resistance. Recent studies in macrophages and zebrafish show that inhibition of mycobacterial efflux pumps with verapamil reduces the bacterial drug tolerance and may enhance drug efficacy. Objectives: Using mice, a mammalian model known to predict human treatment responses, and selecting conservative human bioequivalent doses, we tested verapamil as an adjunctive drug together with standard TB chemotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
127
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(139 citation statements)
references
References 35 publications
12
127
0
Order By: Relevance
“…A detailed analysis of the role of the entire DosR regulon in pathogenesis has not been performed in vivo. We hypothesized that C3HeB/FeJ mice, which develop necrotichypoxic TB granulomas (15) and have been used for studying the efficacy of anti-Mtb (11) and host-directed (14) drugs, would be ideally suited to study if the DosR regulon is required for both the establishment as well as the maintenance of infection in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed analysis of the role of the entire DosR regulon in pathogenesis has not been performed in vivo. We hypothesized that C3HeB/FeJ mice, which develop necrotichypoxic TB granulomas (15) and have been used for studying the efficacy of anti-Mtb (11) and host-directed (14) drugs, would be ideally suited to study if the DosR regulon is required for both the establishment as well as the maintenance of infection in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…C57Bl/6 mice do not faithfully reproduce certain aspects of human TB. In contrast, Mtb-infected C3HeB/FeJ mice display lesions with prominent necrotic degeneration, thus more closely resembling human granulomas (11)(12)(13)(14)(15). Harper and colleagues first demonstrated that tubercle lesions in this model develop hypoxia (15).…”
Section: Clinical Relevancementioning
confidence: 99%
“…Similarly, induction of the macrophage-induced efflux pump Rv1258c confers M. tuberculosis drug tolerance primarily to rifampin, which is reduced by the efflux pump verapamil. Interestingly, the addition of verapamil to the standard anti-TB regimen accelerates bacillary clearance in C3HeB/FeJ mice and significantly lowers relapse rates following 4 months of treatment compared with the case for mice receiving standard therapy alone (305). Recently, semisynthetic analogs of the protein synthesis inhibitor spectinomycin were found to have potent activity against drugsusceptible and drug-resistant M. tuberculosis, at least in part due to chemical modification, which allows the drugs to evade the Rv1258c efflux pump (306).…”
Section: Antimicrobial Efflux Pumps and Drug Tolerancementioning
confidence: 99%
“…As previously described, treatment efficacy was assessed by lung CFU during treatment and relapse rates were measured 3 months after treatment cessation (Table 2) (44).…”
Section: Methodsmentioning
confidence: 99%
“…At each sacrifice point, at least 3 lungs from each group were examined for gross pathology as previously described (44). For histopathological assessments, at least 3 lungs were fixed in either 10% neutral buffered formalin or 4% paraformaldehyde for 3 days.…”
Section: Methodsmentioning
confidence: 99%